2018
DOI: 10.1016/j.autrev.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The use of interleukin 1 receptor antagonist (anakinra) in Kawasaki disease: A retrospective cases series

Abstract: Anakinra used late in the disease course led to a rapid and sustained improvement in clinical and biological inflammation. Our retrospective analysis did show neither a striking nor a rapid decrease of coronary dilatations and we cannot determine if anakinra itself had an effect on coronary artery dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 26 publications
1
66
0
4
Order By: Relevance
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…In highly refractory cases, plasma exchange, cytotoxic agents, or other biologicals have been used [28]. There are a few recent reports of successful use of the IL-1 receptor antagonist, anakinra, for the treatment of highly refractory KD [64].…”
Section: Treatment Options For Resistant Kdmentioning
confidence: 99%
“…Anakinra treatment in this case was 10 weeks [12]. In contrast to these cases, however a retrospective case series published in January 2018 analyzed multiple cases and found that anakinra showed "neither a striking nor a rapid decrease of coronary dilations" and could not determine if anakinra itself had effects on the CAA [13].…”
Section: Discussionmentioning
confidence: 72%